Aberration of Mind : Suicide and Suffering in the Civil War-Era South - Sommerville, Diane Miller (Book collections on Project MUSE., 2018)
This book studies the meaning of suicide in the nineteenth-century South and how that meaning changed, if at all, as a result of the Civil War and its aftermath. It looks at the whole South while providing a more thorough examination than previous books of the dynamics of both the racial and gendered dimensions of suicide in the South during the long Civil War Era.